Efisiensi Dan Efektivitas Anggaran Belanja Pada Rumah Sakit Umum Daerah Cicalengka Kabupaten Bandung - Yoga Pratama; Faizal Pikri (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
This journal discusses the efficiency and effectiveness of the budget for the Regional Public Service Agency with a case study at the Cicalengka Regional General Hospital in Kabupaten Bandung. Efficiency and effectiveness become a necessity for regional public service bodies because in their services they are required to provide optimal and best services without seeking certain benefits. This study aims to determine the realization of the budget of general hospitals in Bandung district cicalengka by analyzing the efficiency and effectiveness of the expenditure budget, as well as knowing the factors that cause the realization is not achieved optimally and know what are the obstacles in the implementation of the budget and efforts in solving problems on the realization of the budget. The results of the analysis show that the efficiency in the budget of general hospitals in Cicalengka is in the quite efficient category and the effectiveness analysis shows the results in the ineffective category due to the inadequate utilization and planning in optimizing the budget and the lack of available budget in meeting the needs of the hospital.